Anticoagulation Strategies in Venovenous Hemodialysis in Critically Ill Patients: A Five-Year Evaluation in a Surgical Intensive Care Unit - Christoph Sponholz; Ole Bayer; Björn Kabisch; Karin Wurm; Katharina Ebert; Michael Bauer; Andreas Kortgen (The Scientific World Journal)
Renal failure is a common complication among critically ill patients. Timing, dosage, and mode of renal replacement (RRT) are under debate, but also anticoagulation strategies and vascular access interfere with dialysis success. We present a retrospective, five-year evaluation of patients requiring RRT on a multidisciplinary 50-bed surgical intensive care unit of a university hospital with special regard to anticoagulation strategies and vascular access. Anticoagulation was preferably performed with unfractionated heparin or regional citrate application (RAC). Bleeding and suspected HIT-II were most common causes for RAC. In CVVHD mode filter life span was significantly longer under RAC compared to heparin or other anticoagulation strategies (P=0.001). Femoral vascular access was associated with reduced filter life span (P=0.012), especially under heparin anticoagulation (P=0.015). Patients on RAC had higher rates of metabolic alkalosis (P=0.001), required more transfusions (P=0.045), and showed higher illness severity measured by SOFA scores (P=0.001). RRT with unfractionated heparin represented the most common anticoagulation strategy in this study population. However, patients with bleeding risk and severe organ dysfunction were more likely placed on RAC. Citrate provided longer filter life spans regardless of vascular access site. Attention has to be paid to metabolic disturbances.